The Neural Network of Neuropeptide S (NPS): Implications in Food Intake and Gastrointestinal Functions - Luca Botticelli; Emanuela Micioni Di Bonaventura; Massimo Ubaldi; Roberto Ciccocioppo; Carlo Cifani; Maria Vittoria Micioni Di Bonaventura (MDPI AG, 2021)
The Neuropeptide S (NPS), a 20 amino acids peptide, is recognized as the endogenous ligand of a previously orphan G protein-coupled receptor, now termed NPS receptor (NPSR). The limited distribution of the NPS-expressing neurons in few regions of the brainstem is in contrast with the extensive expression of NPSR in the rodent central nervous system, suggesting the involvement of this receptor in several brain functions. In particular, NPS promotes locomotor activity, behavioral arousal, wakefulness, and unexpectedly, at the same time, it exerts anxiolytic-like properties. Intriguingly, the NPS system is implicated in the rewarding properties of drugs of abuse and in the regulation of food intake. Here, we focus on the anorexigenic effect of NPS, centrally injected in different brain areas, in both sated and fasted animals, fed with standard or palatable food, and, in addition, on its influence in the gastrointestinal tract. Further investigations, regarding the role of the NPS/NPSR system and its potential interaction with other neurotransmitters could be useful to understand the mechanisms underlying its action and to develop novel pharmacological tools for the treatment of aberrant feeding patterns and obesity.